1975
DOI: 10.1002/aic.690210410
|View full text |Cite
|
Sign up to set email alerts
|

Trickle‐bed reactor performance. Part I. Holdup and mass transfer effects

Abstract: Liquid holdup and mass transfer rates were measured in a 2.58‐cm I.D. tube, packed with glass beads and granular CuO · ZnO catalyst or β‐naphthol particles, and operated as a trickle bed. Gas‐to‐liquid (water) transport coefficients were determined from absorption and desorption experiments with oxygen at 25°C and 1 atm. Liquid‐to‐particle mass transfer was studied using β‐naphthol particles. Holdup and both mass transfer coefficients were unaffected by gas flow rate but increased with liquid rate. The data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
111
1
7

Year Published

1976
1976
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(129 citation statements)
references
References 12 publications
10
111
1
7
Order By: Relevance
“…Since the extent of approach to equilibrium (System A) or the reaction conversion (System B) was lower than 20%with a few exceptions, the maximumerror due to the plug-flow assumption was estimated to be (2) if the boundary layer length along the surface L and the characteristic velocity Ue are suitably defined. Fluid flow may be well characterized by the interstitial velocity U.=Utle (3) Karabelas, Wegner and Hanratty5) showed that a boundary layer which has developed from the nodal point is destroyed once near the contact point and that a second boundary layer develops newly from that point.…”
Section: Methodsmentioning
confidence: 99%
“…Since the extent of approach to equilibrium (System A) or the reaction conversion (System B) was lower than 20%with a few exceptions, the maximumerror due to the plug-flow assumption was estimated to be (2) if the boundary layer length along the surface L and the characteristic velocity Ue are suitably defined. Fluid flow may be well characterized by the interstitial velocity U.=Utle (3) Karabelas, Wegner and Hanratty5) showed that a boundary layer which has developed from the nodal point is destroyed once near the contact point and that a second boundary layer develops newly from that point.…”
Section: Methodsmentioning
confidence: 99%
“…3 shows some of the curves calculated by Eq. (8). The impulse response is characterized by a sharp peak and a tail.…”
Section: Mathematical Model and Methods Of Data Analysismentioning
confidence: 99%
“…The authors developed an isothermal one-dimensional axial dispersion model accounting for external and internal mass transfer, ignoring catalyst wetting. The gas to liquid and liquid to solid mass transfer coefficients were obtained by correlating experimental data at 25°C and 0.1 MPa and can be found in [228]. The model systematically over-estimated the experimental conversions measured for both acids.…”
Section: Steady State Reactor Modellingmentioning
confidence: 99%
“…The possible influence of gasliquid hydrodynamics including partial wetting, axial dispersion and liquid maldistribution as well as external and internal mass transfer parameters was first checked by the diagnose criteria established for three-phase catalytic reactors [224]. The criteria values calculated for the highest temperature of 160°C using appropriate high-pressure literature correlations for the calculation of wetting efficiency [225,226], gas-liquid [227] and solid-liquid [228,229] Table 15 infers that mass transfer should not limit the overall reaction rate. The a gl , a ls and Weisz-Prater U WP criteria based on observed reaction rates showed all low values close to the limit values established for the absence of the respective mass transfer contribution [224].…”
Section: Cwao Kinetic Modellingmentioning
confidence: 99%